Comparison of Aortitis Versus Noninflammatory Aortic Aneurysms Among Patients Who Undergo Open Aortic Aneurysm Repair. Issue 7 (5th June 2020) - Quimson, Laarni; Mayer, Adam; Capponi, Sarah; Rea, Bryan; Rhee, Rennie L.
Abstract : Objective: Distinguishing aortitis‐induced aneurysms from noninflammatory aortic aneurysms is difficult and often incidentally diagnosed on histologic examination after surgical repair. This study was undertaken to examine surgically diagnosed aortitis and identify patient characteristics and imaging findings associated with the disease. Methods: In this case–control study, cases had newly diagnosed, biopsy‐proven noninfectious aortitis after open thoracic aortic aneurysm surgical repair. Five controls were matched with cases for year of surgery and lacked significant inflammation on surgical pathology analysis. Data on comorbidities, demographic characteristics, and laboratory and imaging abnormalities prior to surgery were collected. Associations between exposures and outcomes were evaluated using conditional logistic regression. Backward stepwise logistic regression was used to determine factors independently associated with aortitis. Odds ratios (ORs) with 95%confidence intervals (95%CIs) were calculated. Results: The study included 262 patients (43 patients with aortitis and 219 controls). Patients with aortitis were older at the time of surgery, predominantly female, and less likely to have a history of coronary artery disease (CAD). Multivariable analysis revealed that aortitis was independently associated with an older age at the time of surgery (OR 1.08 [95%CI 1.03–1.13], P < 0.01), female sex (OR 2.36 [95%CI 1.01–5.51], P = 0.04), absence of CAD (OR 6.92 [95%CI 2.14–22.34], P = 0.04), a larger aneurysm diameter (OR 1.74 [95%CI 1.02–2.98], P = 0.04), and arterial wall thickening on imaging (OR 56.93 [95%CI 4.31–752.33], P < 0.01). Conclusion: Among patients who undergo open surgical repair of an aortic aneurysm, elderly women with no history of CAD who have evidence of other aortic or arterial wall thickening on imaging are more likely to have histologic evidence of aortitis. Patients with these characteristics may benefit from further rheumatologic evaluation.